Early anterior crossbite correction through posterior bite opening: a 3D superimposition prospective cohort study. (20th October 2017) - Vasilakos, Georgios; Koniaris, Athanasios; Wolf, Michael; Halazonetis, Demetrios; Gkantidis, Nikolaos
Summary: Objectives: To assess the effectiveness, clinical performance, and potential adverse effects of early anterior crossbite correction through opening of the bite. Subjects and methods: The sample consisted of 16 consecutive patients (8.0 ± 0.9, range: 6.2–9.3 years) with dental anterior crossbite in the mixed dentition who were treated through posterior bite opening. Patients were prospectively followed until a minimum of 6 months post-treatment and there were no drop-outs. Results: In 14 patients (87.5 per cent), the anterior crossbite was corrected. Results remained stable without any retention regime. Active treatment of the successfully treated cases lasted 2.5 months (range: 0.6–8.9). Crossbite correction of central incisors was achieved by a 2.05 mm (range: 0.97–5.45) forward movement and 9.25° (range: 2.32–14.52°) buccal inclination of the crowns ( P < 0.05). The antagonists showed spontaneous adaptation of their position in the opposite direction ( P < 0.05). No important adverse effects were recorded. Limitations: This was a non-comparative controlled study, on a limited sample. Conclusions: Bite opening is a promising, simple, and non-compliance approach for early dental anterior crossbite correction. The technique of 3D superimposition and analysis of digital models used here, allowed precise evaluation of single tooth movement in all three planes of space.